Surgery Alone Versus Surgery Followed by Chemotherapy and Radiotherapy in Resected Extrahepatic Bile Duct Cancer: Treatment Outcome Analysis of 336 Patients - Im, Jung Ho (Cancer Res Treat, 2016)
PURPOSE: This study analyzed the outcomes of patients with resected extrahepatic bile duct cancer (EHBDC) in order to clarify the role of adjuvant treatments in these patients. MATERIALS AND METHODS: A total of 336 patients with EHBDC who underwent curative resection between 2001 and 2010 were analyzed retrospectively. The treatment types were as follows: surgery alone (n=168), surgery with chemotherapy (CTx, n=90), surgery with radiotherapy (RT) alone (n=29), and surgery with chemoradiotherapy (CRT, n=49). RESULTS: The median follow-up period was 63 months. The 5-year rates of locoregional failure-free survival (LRFFS), distant metastasis-free survival (DMFS), progression-free survival (PFS), and overall survival (OS) for all patients were 56.5%, 59.7%, 36.6%, and 42.0%, respectively. In multivariate analysis, surgery with RT and CRT was a significant prognostic factor for LRFFS, and surgery with CTx was a significant prognostic factor for DMFS, and surgery with CTx, RT, and CRT was a significant prognostic factor for PFS (p < 0.05). Surgery with CTx and CRT showed association with superior OS (p < 0.05), and surgery with RT had marginal significance (p=0.078). In multivariate analysis of the R1 resection patients, surgery with CRT showed significant association with OS (p < 0.05). CONCLUSION: Adjuvant RT and CTx may be helpful in improving clinical outcomes of patients with resected EHBDC who have a high risk of disease recurrence, particularly R1 resection patients. Conduct of additional prospective, larger-scale studies will be required in order to confirm the benefit of adjuvant RT and CTx in these patients.